TOURISM POTENTIAL IN NOVEL RONGGENG DUKUH PARUK BY AHMAD TOHARI - Aftina Aftina; Taufik Dermawan; Wahyudi Siswanto (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
The rising income of tourism sector in Belitung since the succeeded Laskar Pelangi novel and film, encourages the researcher to investigate the tourism potential in a literary works that is similar with the novel. A novel entitled Ronggeng Dukuh Paruk was chosen because the novel sets out the unique nature and culture in Banyumas, therefore it has succeeded in attempting Indonesian literary observers, both domestic and foreigners.  The research aimed to explore the potential of natural and craft tourism in Ronggeng Dukuh Paruk. The research used a mimetic approach supported by the theories and concepts of tourism literature.  The data was collected through documentation and textual analysis guided by instruments and data tables according to the research focus, which are (1) nature tourism and (2) craft tourism.